Karakterisasi Sifat Termofisika Paduan Titanium Ti6Al4V - Tajalla, Gusti Umindya Nur; Ismail, Andi Idhil (Jurnal Rekayasa Mesin, 2020)
Manufacturers are pushed to use superalloys such as titanium alloys in the aerospace part due to environmental and economic issues. The refractory properties of titanium alloys result in rapid and premature wear of the cutting tools, especially by thermal diffusion. Therefore, the purpose of this paper is to focus on understanding the characterization of TiAl6V4 in thermo-physic properties. X-ray diffraction (XRD), scanning electron microscope (SEM), electrical resistivity against temperature test, and differential scanning calorimetry (DSC) were conducted to analyze the relationship of phase transformation to thermal properties. Phase analysis showed that TiAl6V4 is composed of two-phase a and b creating a duplex microstructure in which the surface fraction contains about 92,5 % and 7,5 %, respectively. Electrical resistivity against temperature test demonstrated the phase transformation of a to b occurred at 1017Â°C. This study revealed that the phenomena of phase transformation affected the thermal properties, i.e., thermal capacity, thermal diffusivity, and coefficient of thermal expansion.